The house in Zurich where Lenin stayed from February 21, 1916 until April 2, 1917 'aufgenomen für Karl Korsch Februar 1953'
The house in Zurich where Lenin stayed from February 21, 1916 until April 2, 1917 'aufgenomen für Karl Korsch Februar 1953'.